Sociofunctionalism in diachrony: dilemmas, conjectures and applications - Coan, Márluce (2021)
Based on sociofunctionalist assumptions, we present dilemmas imposed to the researcher, specifically those aimed at the starting point (from the function to the form or vice versa) and the notion of meaning (referential or by functional domain). Conjectures are then exposed to solve these dilemmas with regard to the analysis of the function of antepretérito codified by ‘pretérito mais-que-perfeito simples’, ‘haver/ter’ in the imperfective form plus participle neutral, ‘pretérito anterior’ and the simple past tense. Then we analyzed this phenomenon qualitatively and quantitatively in data from historical, literary, religious and legal prose from Galician-Portuguese, considering data from the 13th to 15th centuries, obtained in “Tesouro Medieval Informatizado da Língua Galega”. The investigation proves variation motivated by factors related to type of verb, time marker, discursive person, clause type, polarity, kind of object (in cases of ‘haver/ter’ in the imperfective plus participle neutral) and type of prose, whereas shows grammaticalization processes.